Internal model controller design via H dynamic output feedback - Yaman, S.; Ustoglu, I.; Ucun, L. (SAGE PUBLICATIONS LTD, 2017)
This paper deals with internal model controller design via dynamic output feedback for linear perturbed systems. The study proposes an internal model controller within the perspective of dynamic output feedback, utilizing a linear matrix inequality based optimization algorithm. This proposed method is a synthesis of an internal model controller design that has different application fields, as reported in the literature, and an dynamic output feedback controller, which has proven its success in several studies. The proposed controller attenuates disturbances, having bounded energies on controlled output. The originality of the work lies in the combination of two different approaches to obtain an optimal controller design algorithm. The liability and performance of the proposed method are illustrated via simulations, which are applied to a couple of benchmark problems.
Keywords: Internal model control; H controller design; dynamic output feedback controller; INFINITY CONTROL; PRINCIPLE; SYSTEMS; Automation & Control Systems; Instruments & Instrumentation